Internet of Things Implementation of Nitrate and Ammonium Sensors for Online Water Monitoring - Agir, Ismail; Yildirim, Ridvan; Nigde, Mustafa; Isildak, Ibrahim (SPRINGERNATURE, 2021)
In this work, we proposed a new wireless sensor to contribute to research aimed at continuous monitoring of nitrate and ammonium in water, which as leading agents of water pollution have become the source of a serious problem today. In this research, a well-implemented application of an electroanalytical sensor was achieved by combining it with the internet of things (IoT) concept, which is the most modern technique for wireless data collection. We developed a portable IoT system and ion-selective nitrate and ammonium electrodes and monitored the nitrate and ammonium levels of the water online. The system was produced in a low-cost manner (under $25) and it enabled data acquisition without energy-related problems, thanks to the support of solar energy and mobile power bank. The recovery rates of the sensors were tested with the standard addition method and response was obtained between 101.74 and 147.01%.
Keywords: Water quality monitoring; ion-selective electrode; internet of things; ION-SELECTIVE ELECTRODES; NETWORK; BIOSENSORS; PLANT; Chemistry